Introducción a la fotografía hemisférica en ciencias forestales - Díaz, Gastón Mauro (2014)
Hemispherical photography is profusely used in climatology and forest sciences in association with geomatics technology. It is possible to get a detailed record of the canopy and estimate, both of the same structure and understory light transmission, both variables important for forest inventory and management of natural regeneration. Hemispherical photography equipment have very diverse applications, even in artistic photography, and their cost is low compared to specific instruments. Particular knowledge of optics, photography and digital image processing is required to correctly use this technique. The objective of the work is to explain the principle of operation of the hemispherical photography on estimation of structural parameters of forests. This is discussed in terms of optics and photography, digital image processing and estimation of structural parameters. Understanding of these aspects is relevant when it comes to purchasing a computer, capture photographs in the field and use specific software for processing.  Photos are raster files, which can be understood as an array of n rows by m columns, where each cell is a pixel. So a raster is displayed as an image, it is necessary to establish a color space and color depth. It is important to note that in the capture of the photography major errors occur, depending on the geographical region, because it is very difficult to meet the ideal lighting conditions.